2023
DOI: 10.1021/acs.jctc.2c01318
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Interactions in a [Co(II)3Er(III)(OR)4] Model Cubane through Forefront Multiconfigurational Methods

Abstract: Strong electron correlation effects are one of the major challenges in modern quantum chemistry. Polynuclear transition metal clusters are peculiar examples of systems featuring such forms of electron correlation. Multireference strategies, often based on but not limited to the concept of complete active space, are adopted to accurately account for strong electron correlation and to resolve their complex electronic structures. However, transition metal clusters already containing four magnetic centers with mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 90 publications
(332 reference statements)
0
16
0
Order By: Relevance
“…This will be the subject of a future publication. In a series of recent works, ,, we have shown that by simple orbital localizations and reorderings, it is possible to obtain CI Hamiltonian matrices with a unique and unprecedented block diagonal structure. As a consequence, extremely compact wave functions (to the limit of near-single-reference) are obtained for ground and excited states of exchange-coupled polynuclear transition metal clusters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This will be the subject of a future publication. In a series of recent works, ,, we have shown that by simple orbital localizations and reorderings, it is possible to obtain CI Hamiltonian matrices with a unique and unprecedented block diagonal structure. As a consequence, extremely compact wave functions (to the limit of near-single-reference) are obtained for ground and excited states of exchange-coupled polynuclear transition metal clusters.…”
Section: Discussionmentioning
confidence: 99%
“…The full configuration interaction quantum Monte Carlo (FCIQMC) method is a sparse and highly parallelizable CI eigensolver in quantum chemistry. , Relying on the sparsity of the CI Hamiltonian and its eigensolutions, FCIQMC is in general not limited by the active space sizes, in contrast to conventional CI methods, , which are limited to at most 18 electrons and 18 orbitals . Due to the nearly linear parallelization of the algorithm, FCIQMC takes full advantage of modern computer architectures and allows a large number of electrons and orbitals to be explicitly correlated; active spaces containing up to 96 electrons in 159 orbitals have been reported to date .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Provided that the perturbation would not cause a significant adjustment of the |ψ (0) ⟩ amplitudes, reducing the dimensionality of the FOIS does not affect the energy correction substantially; however, if the zeroth-order description is flawed, this approximation breaks down. Practical examples include the V -state of ethene or many instances of transition-metal clusters. ,,,, …”
Section: Theorymentioning
confidence: 99%
“…The size of the virtual space also limits the naive application of the uncontracted perturbation theory that uses a perturber space whose size is directly proportional to the length of the reference expansion. The effective Hamiltonian formalism based on Löwdin’s partitioning technique allows to describe the influence of a perturbation on a model space without changing the dimension of the zeroth-order problem, transferring the computational burden on the calculation of the transfer matrix. , Through the model space Quantum Monte Carlo method, this cost can be greatly reduced. Other approaches such as MC-PDFT , or transcorrelation promise to alleviate the dependence on the orbital expansion by describing dynamic correlation based on the on-top pair density or Jastrow factors, respectively.…”
Section: Introductionmentioning
confidence: 99%